S59 Epithelial immune activation and intracellular invasion by non-typeable Haemophilus influenzae. (11th November 2022) - Brown, MA; Morgan, SB; Donachie, G; Horton, KL; Pavord, ID; Arancibia, C; Hinks, TSC
Abstract : Background: Type-2 low asthma affects 30–50% of patients in severe asthma clinics and includes a phenotype characterised by sputum neutrophilia and resistance to therapeutic corticosteroids. Airways inflammation in such individuals may be driven by persistent bacterial colonisation of the lower airways by organisms such as non-encapsulated strains of the gram-negative bacterium Haemophilus influenzae (NTHi). Although considered a pathogen in the lower airways, NTHi is a commensal of the upper airways. It is not known to what extent these strains can invade airway epithelial cells, persist intracellularly and activate epithelial cell production of proinflammatory cytokines, and how this differs between the upper and lower airways. Methods: We studied NTHi infection of primary human bronchial epithelial cells (PBEC), primary nasal epithelial cells (NECs) and epithelial cell lines (Calu-3, RPMI2650, BEAS2-B) from upper and lower airways grown in submerged and air-liquid interface cultures. Bronchoscopies were performed on healthy volunteers according to established SOPs after ethical approval (18/SC/0361 and 08/H0402/189) and written informed consent. Adherent, paracellular and internalised bacteria were enumerated by gentamicin exclusion assays, and confirmed by confocal microscopy. Cytokines and signalling pathways were evaluated by qPCR, and Fluidigm PCR array, whilst cytokine production was confirmed by ELISA. Results: We found NTHi was internalised within PBEC at 6 hours, but live intracellular infection did not persist at 24 h. NTHi strains differed in their propensity for intracellular and paracellular invasion. Confocal microscopy and flow cytometry showed NTHi infected secretory, ciliated and basal PBEC. Infection of PBEC led to induction of CXCL8, interleukin (IL)-1b, IL-6 and TNF. The magnitude of cytokine induction was independent of the degree of intracellular invasion differing by strain-specific propensity to invasion or by cytochalasin D inhibition of endocytosis, with the exception of the inflammasome-induced mediator IL-1b. NTHi-induced activation of TLR2/4, NOD1/2 and NLR inflammasome pathways was significantly stronger in NEC than in PBEC. Conclusions: Together our data suggest that NTHi can be internalised transiently by airway epithelial cells and has capacity to drive inflammation in airway epithelial cells of the lower and upper airway. Please refer to page A210 for declarations of interest related to this abstract.